AH-01 Is There Macroscopic Different Appearance in Using Formalin with Low and High Concentration in Technic of Cadaver Embalming? - Ria Margiana (Media Veteriner, 2015)
Is There Macroscopic Different Appearance in Using Formalin with Low and High Concentration in Technic of Cadaver Embalming?